Hydrodynamic Drag during Gliding in Swimming - Marinho, Daniel (2020)
Submitted by Daniel Marinho (dmarinho@ubi.pt) on 2020-02-12T22:49:48Z No. of bitstreams: 1 107 - marinho2009.pdf: 178858 bytes, checksum: 45a05c939570b6313f7f99b4e7e149fb (MD5)